Public Communication Model In Combating Hoaxes And Fake News In Ahead Of The 2024 General Election - ISKANDAR, Dudi; SURYAWATI, Indah; SURATNO, Geri; LILIYANA, Liliyana; MUHTADI, Muhtadi; NGIMADUDIN, Ngimadudin (PT Keberlanjutan Strategis Indonesia, 2023)
Political discourse preceeding the 2024 General Election has led to the contamination of the media landscape with hoaxes and fakenews. The public, candidates, and state actors not only compete with factual information and positive news, but also contends with the spread of misinformation and fake news. The prevalence of hoaxes on social media and fake news in mass media circulation prior to the 2024 General Election poses a tangible threat to social unity and national integration. This paper aims to analyze the model of public communication used to combat hoaxes and fakenews before the 2024 General Election done by the Ministry of Communication and Information and other stakeholders. The data for this paper is based on qualitative research carried out with data collection technique through literature searches, observation, and interview. The study discovered that the public communication model developed to combat hoaxes and fake news in advance of the 2024 General election has been ineffective. The fundamental weakness of the public communication model in eradicating hoaxes and fake news lies in the uneven application of the law inforcement and penalties. In addition, there are some elements of the public communication model that do not systematically show significant and consistent progress. At a macro level, this can be understood as the lack of clear roadmap and grand design to eliminate hoaxes and fake news in Indonesia. A clear plan or atrategy is needed for the long term establishment of a culture focused on the eradication of hoaxes and fake news.